A Study on the Perception of Non-English Students’ Toward the Necessary of English - Sholichah, Norma Ita (Universitas Nurul Jadid, 2024)
English is an international language that is widely studied in various countries. However, English is already like a currency, one side of which is considered fun, and the other side is considered complicated and troublesome. Because researchers believe that students need English as an essential element in the modern world, such as education or even work, researchers' perceptions may be different from the perceptions of students so different perceptions will emerge from one person to the other. To analyze this, the researchers put Al-Qolam students of non-English-language Tarbiyah Faculty as objects. The study aims to know perceptions of the necessary of English and also to know the English language needs of Al-Qolam students of Non-English Tarbiyah Faculty.So, it can be found and concluded that many of the students give a positive perception, not just English students who need expertise in English. However, even non-English students realize that English is important and needed. Because they also need learning resources, books, and journals that use English. To help the process and development of their studies. Students also have the perception that English is not only needed at the time of learning but English is also needed for the future. Then it was discovered that it was important to have an analysis of the needs of students in a learning process. So, the researchers found that Al-Qolam students need a skill in reading. According to the student's perception, the skill of reading can help the process of teaching needed to help understand the learning sources, books, or journals that use the English language. With that skill of reading, students acquire knowledge and add vocabulary automatically.